2014
DOI: 10.1074/jbc.m114.586966
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Control of Glycine Transporter 2 (GlyT2) by Physical and Functional Association with Plasma Membrane Ca2+-ATPase (PMCA) and Na+-Ca2+ Exchanger (NCX)

Abstract: Background: GlyT2 is crucial for glycinergic neurotransmission, but only a few interacting partners for this protein are known. Results: PMCA2/3 and NCX1 interact with GlyT2 and modulate its activity in lipid raft subdomains. Conclusion: Functional interaction of GlyT2 with PMCA2/3 and NCX1 helps Na ϩ and Ca 2ϩ local homeostasis in glycinergic terminals. Significance: Learning how GlyT2 is regulated might help with developing new therapies for hyperekplexia or neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 98 publications
0
23
0
Order By: Relevance
“…These values were corrected against local background staining and compared to neighboring untransfected somas to correct for variations in global staining intensity. Immunocytochemistry to ensure expression of STIM1-myc or D76A/E87A STIM1-myc in STIM1-KD neurons using an antibody against the myc tag (mouse, Abcam, #ab18185; 1:500) was performed as described previously (de Juan-Sanz et al, 2014), visualized using an Alexa-546 anti-mouse secondary antibody (Life Technologies).…”
Section: Star Methodsmentioning
confidence: 99%
“…These values were corrected against local background staining and compared to neighboring untransfected somas to correct for variations in global staining intensity. Immunocytochemistry to ensure expression of STIM1-myc or D76A/E87A STIM1-myc in STIM1-KD neurons using an antibody against the myc tag (mouse, Abcam, #ab18185; 1:500) was performed as described previously (de Juan-Sanz et al, 2014), visualized using an Alexa-546 anti-mouse secondary antibody (Life Technologies).…”
Section: Star Methodsmentioning
confidence: 99%
“…Then, GlyT2 is sorted to the plasma membrane in lipid rafts, microdomains where it interacts with proteins like neuronal plasma membrane Ca 2+ -ATPase (PMCA), and Na + /Ca 2+ -exchanger 1 (NCX1). Endogenous PMCA and NCX activities are necessary for GlyT2 activity and this modulation depends on lipid raft integrity [18]. In neurons, GlyT2 is concentrated at presynaptic elements in a process dependent on the PDZ-interacting motif located in its C-terminus [19].…”
Section: Introduction: the Building Of A Glycinergic Neuronmentioning
confidence: 99%
“…In neurons, LNX1 may act as a presynaptic scaffold, promoting the formation of multimolecular complexes that could allow the correct subcellular localization of GlyT2 and other interacting partners 31,63 . GlyT2 has been previously shown to interact with several presynaptic proteins, including syntaxin1 16 , Plasma Membrane Calcium ATPases PMCA2 and PMCA3 18 and sodium/potassium ATPase subunits α3 (α3NKA) and β2 (β2NKA) 17 . It is possible that LNX1 may act as a scaffold to facilitate the interaction of GlyT2 with the mentioned proteins, and this idea of a GlyT2-LNX1-PMCA/NKA multimolecular complex is supported by a recent proteomic study that found PMCA2 and β2NKA as candidate interacting partners of LNX1 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular regulation of GlyT2 transport would provide insight into the molecular and cellular basis of glycinergic neurotransmission and potentially lead to identifying new therapeutic targets for presynaptic Hyperekplexia. Previous studies on GlyT2 regulatory mechanisms revealed that GlyT2 activity is regulated by PKC activation 10,11 , calnexin function 12,13 , P2Y and P2X purinergic receptors 14,15 and interaction with syntaxin1 16 , Na+/K+-ATPase 17 and PMCAs 18 . In addition, we previously described that GlyT2 trafficking and surface expression are regulated by ubiquitination 11,19 , a process in which the small protein ubiquitin is covalently attached to a cytoplasmic lysine residue of a target protein.…”
Section: Introductionmentioning
confidence: 99%